The role of microcredit funds in promoting the social capital of villagers Case study: Hosseinan Village in Damghan County - Asghar Tahmasebi; Farzaneh Fakhrabadipur (تحقیقات کاربردی علوم جغرافیایی)
In recent years, enhancing social capital and participation of rural communities are taken in consireation in many rural development programs in Iran. The purpose of this study was to investigate the effect of microcredit fund created in the Carbon Sequestration Project on the promotion of social capital of the community member in the Hosseinan village in Damghan. To this end, the level of participation and social interaction of the members of four rural development groups before and after the project implementation was analyzed using social network analysis method. The required data were collected through participatory workshop from whole network members of 38 people in 4 randomly selected groups. Bootstrap test was used to compare the density and centrality of the network before and after  the project implementation. The results show statistically significant (P<05) increase in density and centralization of the collaboration network after the project implementation. The project also succeeded in attracting the participation of people with different levels of education, and there was no significant difference in the degree centrality people with different educational groups. Similarly, the project has had a significant impact on the creation of coherence between the development groups of the village of Hosseinan.